Energy generation in a hybrid harvester under harmonic excitation. (1st January 2018) - Rajarathinam, M.; Ali, S.F.
Highlights: A coupled piezoelectric and electromagnetic hybrid energy harvester is proposed for broader energy harvesting. A simplified 2-DoF analytical model is developed which provides a good approximation to the experimental results. Parametric studies are carried out to determine the influence of mechanical and electrical parameters on the harvested power. The present hybrid model can widen the operating bandwidth and it generates high current and high voltage simultaneously. Abstract: A hybrid energy harvester combining piezoelectric and electromagnetic transduction mechanisms is designed to harvest vibration energy. The system comprises of a cantilever beam PZT harvester and a magnetic mass hung through a spring at the free end. The beam with PZT harvests energy using piezoelectric effect while the hanging mass oscillates through a copper coil to harvest electromagnetic energy. This paper studies power harvested from the hybrid harvester under harmonic excitation using experimental and analytical evaluations. Comparisons are made with the standalone piezoelectric and electromagnetic harvesters under similar excitation environment. The study shows that the present hybrid harvester can harvest energy at a broad range of frequencies. Furthermore, a few parametric studies are carried out to understand the device output performance. The bandwidth of the harvester and the power harvested within the bandwidth can be designed based on the stiffness of the system and also by changing the electromechanical coupling coefficient. Studies reported also show that bandwidth of harvester can also be increased by increasing the magnetic mass.